EVALUASI KUALITAS PELAYANAN PUBLIK BERDASARKAN INDEKS KEPUASAN MASYARAKAT DI KELURAHAN KEPUHKIRIMAN KABUPATEN SIDOARJO - Adrian Arthur Normandy (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2026)
This study evaluates community satisfaction with public services at Kepuhkiriman Sub-District, Waru District, Sidoarjo Regency. A descriptive quantitative approach with a survey method was used involving 316 respondents selected through accidental sampling. Data were analyzed using the Community Satisfaction Index (CSI/IKM) based on Ministerial Regulation of Administrative and Bureaucratic Reform No. 14 of 2017 and five SERVQUAL dimensions. The results show that the overall CSI score was 70.4, categorized as satisfied. Assurance obtained the highest score (82; very satisfied), indicating that officer friendliness, clarity of information, and fairness of service were perceived positively. Conversely, tangibles (64; moderately satisfied) and responsiveness (66; moderately satisfied) were the weakest dimensions, mainly due to limited waiting-room facilities, the absence of a digital queuing system, and long waiting times. The study recommends improving physical facilities, implementing digital queuing, increasing service responsiveness, and providing accessible complaint channels.